Reading prisoners : literature, literacy, and the transformation of American punishment, 1700-1845 - Schorb, Jodi, 1966- (Critical issues in crime and society., 2014)
Shining new light on early American prison literature-from its origins in last words, dying warnings, and gallows literature to its later works of autobiography, exposé, and imaginative literature-Reading Prisoners weaves together insights about the rise of the early American penitentiary, the history of early American literacy instruction, and the transformation of crime writing in the "long" eighteenth century. Looking first at colonial America-an era often said to devalue jailhouse literacy-Jodi Schorb reveals that in fact this era launched the literate prisoner into public prominence.